(untitled) (KASBIT Business Journal, 2012)
The research is being conducted to overview and emphasize on the comparative study of local banks to identify the effects of total quality management (TQM) in the banks to evaluate the financial performance which they are providing to their customers. Therefore the main objective of this study is to find out impact of TQM practices on the financial performance of the banks. Literature review reveals that the implementation of TQM practice in Pakistani banks is still at rudimentary level. It was also revealed that implementation of TQM practices lead high quality performance. Exploratory research has been used in order to have a better and deeper understanding of the research problem. Furthermore, since the problem could not be articulated with any precision, the research of an exploratory nature was required, also enabling to develop clear objectives. It took the form of literature searches, informal personal interviews with experienced people who are the bank customers or the bank employees as well as formal questionnaire filling by them. Sample size of 150 individuals has been selected in this research. Out of 150 respondents, 122 respondents have been used for data analysis, and 28 respondents whose responses have not been evaluated because of ambiguity. Comparisons of various service offerings provided by local banks have also been considered for the purpose of evaluating the service quality gaps. The outcomes of this study furthermore display that the use of financial performance assesses has a mediator function in the connection between TQM scheme and value performance. The outcomes furthermore show that an enhancement of value performance positively sways financial performance through improvements in enterprise performance. The banks should start a company’s wide perception of TQM through seminar and workshop. The content of teaching of bank workers should be such that will enhance the implementation of the TQM. Employees’ value perception and engagement through well-developed programmed should be granted broad publicity.